2021
DOI: 10.3390/chemosensors9100276
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin PANI-Decorated, Highly Purified and Well Dispersed Array Cncs for Highly Sensitive HCHO Sensors

Abstract: The flocculation of small surficial groups on pristine CNCs (carbon nanocoils) bundles limit their application. In this study, we designed and fabricated novel array CNCs with a surficial decoration of polyaniline (PANI) using in situ methods. Atomic layer deposition (ALD) and chemical vapor deposition (CVD) methods were employed to fabricate the highly pure array CNCs. The array CNCs decorated with ultra-thin PANI were confirmed by different characterizations. Furthermore, this material displayed a good perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The morphology of the heterostructures may have an influence on the sensor properties. It has been reported that the confined space within hollow SnO 2 nanocoils after functionalization of ALD NiO enhances the gas adsorption on the surface and improves the sensing performance [30,53]. In air, oxygen chemisorbs onto the surface of MOS materials to form surface oxygen species (O 2 − , O − and O 2− ) [54,55].…”
Section: Sensing Mechanism Of Mos Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of the heterostructures may have an influence on the sensor properties. It has been reported that the confined space within hollow SnO 2 nanocoils after functionalization of ALD NiO enhances the gas adsorption on the surface and improves the sensing performance [30,53]. In air, oxygen chemisorbs onto the surface of MOS materials to form surface oxygen species (O 2 − , O − and O 2− ) [54,55].…”
Section: Sensing Mechanism Of Mos Heterostructuresmentioning
confidence: 99%
“…Moreover, ALD is also very effective in depositing metal catalysts, which can be uniformly loaded onto various sensor materials and improve the gas sensing performance [26]. Due to these unique characteristics, ALD is capable of not only synthesizing novel sensor materials, but also manufacturing gas sensor devices with high reproducibility and uniformity [27][28][29][30]. Materials deposited by ALD on a MOS host can be noble metals or MO, either as nanoparticles anchored on the MOS surface or as a conformal coating layer over the MOS structures.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of the QCM sensor refers to the previous work of our research group [37][38][39], replaced with MOF-14 samples. Testing of the QCM sensor included three steps: (1) baseline obtained by purging with high-purity synthetic air; the gas to be tested was introduced only after the baseline was stable (when the frequency drift does not exceed 5 Hz).…”
Section: Fabrication Of Qcm Sensors and Measuring Equipmentmentioning
confidence: 99%